Pomegranate By‐Products in Colorectal Cancer Chemoprevention: Effects in Apc‐Mutated Pirc Rats and Mechanistic Studies In Vitro and Ex Vivo. Issue 2 (22nd November 2017) - Tortora, Katia; Femia, Angelo Pietro; Romagnoli, Andrea; Sineo, Irene; Khatib, Mohamad; Mulinacci, Nadia; Giovannelli, Lisa; Caderni, Giovanna
Abstract : Scope: To investigate the effect of pomegranate mesocarp, a polyphenol‐rich by‐product of juice production, in colorectal cancer (CRC) chemoprevention. Methods and results: A mesocarp decoction (PMD) is administered for 6 weeks in the diet to Pirc rats, mutated in Apc, a key‐gene in CRC. Mucin‐depleted foci (MDFs), as CRC biomarkers, are reduced in PMD‐fed rats compared to controls (MDF/colon: 34 ± 4 versus 47 ± 3, p = 0.02). There is an increase in apoptosis in MDFs from PMD‐treated rats compared to controls (2.5 ± 0.2 versus 1.6 ± 0.2, p  < 0.01). To elucidate the involved mechanisms, two colon‐relevant metabolites of the polyphenolic and fiber PMD components, urolithin‐A (u‐A) and sodium butyrate (SB), are tested alone or in combination in vitro (colon cancer cells), and ex vivo in adenoma (AD) and normal mucosa (NM) from Pirc rats. u‐A 25 μ m plus SB 2.5 mm (USB) causes a significant reduction in COX‐2 protein expression compared to untreated controls (about –70% in cancer cell cultures, AD, and NM), and a strong increase in C‐CASP‐3 expression in cells (about ten times), in AD and NM (+74 and +69%). Conclusion: These data indicate a chemopreventive activity of PMD due, at least in part, to pro‐apoptotic and anti‐inflammatory action of its metabolites that could be exploited in high‐risk patients. Abstract : Pomegranate mesocarp (PMD), a polyphenol‐rich by‐product of juice production, reduces colon carcinogenesis in Apc ‐mutated rats and increases apoptosis (cell death) in precancerous lesions. Two main metabolites of PMD, u‐A and butyrate, alone or in combination reduce inflammation and increase apoptosis in cancer cell lines or in adenoma and normal mucosa from rats. The data indicate a preventive activity of PMD that could be exploited in patients at high risk for colon cancer.